The night, the thought and the river - Rodríguez Víquez, Mónica (2016)
The present literary work is developed in the Middle Age, with the goal of developing an analysis of the historical facts of China, specifically in the Tang dynasty from the year 618 to the year 907, which is a period of unification, rise and flourish in the territory. Through a peasant estate fictional male character, where we intend to reveal his daily life, like it’s room, family, occupation, diet, among other elements; at the same time, the collective mentalities according to aspects of religion and their perception of the political, social and economic system. In addition, we take into account the microhistory of populations that were traditionally omitted, as it is the low social class, we put in evidence the discrimination, oppression, inequality, exams system, hierarchies, the role of the man and woman, marriage, commerce, urban development, love, among other characteristics of the era.